Cinnamaldehyde in Focus: Antimicrobial Properties, Biosynthetic Pathway, and Industrial Applications - Brandon Armando Jaramillo Jimenez; Fatima Awwad; Isabel Desgagné-Penix (MDPI AG, 2024)
Trans-cinnamaldehyde (TCA), a major bioactive compound derived from cinnamon (Cinnamomum spp.), has garnered significant attention for its diverse therapeutic properties. Its broad-spectrum antimicrobial activity, targeting both Gram-positive and Gram-negative bacteria as well as various fungi, positions TCA as a potent natural antimicrobial agent. Beyond its antimicrobial effects, TCA demonstrates promising antidiabetic and anti-inflammatory activities, making it a valuable compound in medicinal and cosmetic applications. Recent studies have highlighted its role in disrupting microbial membranes, inhibiting biofilm formation, and modulating key metabolic pathways in pathogens. Furthermore, TCA has gained popularity in cosmetics due to its antimicrobial activity, antioxidant properties, and skin-friendly profile. This review provides a comprehensive overview of TCA's antimicrobial potential, focusing on its mechanisms of action and its market and industrial applications. We also discuss the biosynthetic pathway of TCA, exploring both its natural production in cinnamon and advances in biotechnological production methods. As the demand for sustainable and natural antimicrobial agents grows, TCA emerges as a promising candidate for diverse applications. Finally, this review explores future directions for optimizing TCA production through metabolic engineering and synthetic biology approaches to meet industrial-scale demands.